Management of frailty at individual level - Frailty prevention - Branko Gabrovec; Brigita Skela-Savič (Nurses and Midwives Association of Slovenia, 2018)
Introduction: Frailty is a geriatric syndrome characterized by a diminished physiological reserve of multiple organs, which means increased of vulnerability of older people to adverse outcomes. As the process which leads to frailty can be decelerated or even completely reversed, early prevention interventions are crucial. Methodology: A systematic literature search was conducted in the following databases: PubMed, Cochrane, Embase, Cinahl and  UpToDate. The criterion in selecting the literature was that articles were published from 2002 to 2017. From 391.910 initial hits, 31 publications were selected. Results: Early diagnosis of frailty and functional decline are considered effective measures against age-related comorbidities. Targeted interventions have a significant impact on preventing the progression of frailty and the negative consequences of frailty. Lifestyle, including physical activity (particularly resistance exercise) and nutrition (higher protein intake and vitamin D supplement), is a good measure for preventing disorders associated with age. Conclusion: Targeted interventions have a significant modifiable influence on preventing frailty. Frailty management and early interventions comprise comprehensive and multidisciplinary approach including clinical management with physical management, nutrition and drugs.